Maintenance of immune response throughout childhood following serogroup c meningococcal conjugate vaccination in early childhood. (24th May 2012) - Khatami, A; Pollard, AJ; Peters, A; Robinson, H; Thompson, A; Findlow, H; Snape, MD
Abstract : Background: Serogroup C meningococcal (MenC) conjugate vaccines were introduced into the UK routine infant immunisation schedule in 1999, along with a "catch-up" campaign for those aged 1–25 years. Previous cross-sectional studies demonstrated children immunised in early childhood have lower MenC bactericidal antibody 5 years after immunisation than children immunised in late childhood, however the kinetics of antibody decline through childhood have not been evaluated in a longitudinal study. We aimed to evaluate the kinetics of antibody decline through childhood in a longitudinal study of a single cohort following a dose of MenC conjugate vaccine in early childhood, and to calculate the proportion of 11 to 13 year-olds with protective levels of bactericidal antibody 10 years after immunisation. Method: Stored sera obtained at multiple time-points between 2001 and 2010 from children who had received a single dose of MenC vaccine at age 1 to 3.5 years, were analysed for MenC serum bactericidal antibody using rabbit complement (rSBA). Results: The MenC rSBA geometric mean titre (GMT) at age 3.5 to 5 years, approximately one year after immunisation, was 8.0 (95% confidence interval [CI] 6.5-9.9, n = 292). Over the subsequent 9 years, rSBA GMT declined to 3.3 (CI 2.5-4.4, n = 98) at age 11.5-13.5 years. The percentage of children with rSBA titres >1:8 (threshold for protection) also declined from 38% (CI 35%-41%) to 15% (CI 12%-19%). Conclusion: MenC rSBA titres wane rapidly following vaccination in early childhood, without evidence of natural boosting of antibody levels through cross-reactive antigens. In the UK, consideration should be given to a routine adolescent booster of MenC vaccine to protect this cohort of children who are entering the potentially high risk period of adolescence, and to prevent a resurgence in nasopharyngeal carriage and maintain herd immunity.